Postsecondary play : the role of games and social media in higher education - Tierney, William G. (Tech.edu., 2014)
Part of the barrier to college access is navigating the elaborate application process with its multiple essays, test scores, and deadlines. For students without substantial school and family support, this is enough to make entering college impossible.